Effects of tyrosine kinase inhibitor therapy on skin toxicity and skin-related quality of life in patients with lung cancer: An observational study. Issue 23 (5th June 2020) - Tseng, Li-Chuan; Chen, Kang-Hua; Wang, Chih-Liang; Weng, Li-Chueh
Abstract : Abstract: Epidermal growth factor receptor tyrosine kinase inhibitor (EGFR-TKI) therapy is the primary treatment option for patients with non-small cell lung cancer (NSCLC). However, one of the major adverse effects associated with this therapy is skin toxicity, which impacts the patient's quality of life. This study aimed to describe the severities and locations of skin toxicity, and to analyze their association with the quality of life in patients with advanced NSCLC who received EGFR-TKI therapy as first-line treatment. This cross-sectional and correlation study was conducted at a tertiary medical center in northern Taiwan between July 2015 and March 2016. Skin toxicity was assessed and graded using the National Cancer Institute Common Terminology Criteria for Adverse Events (version 4.03). The Skindex-16 scale was used to measure the skin disease-related quality of life. A total of 146 NSCLC patients who received EGFR-TKI therapy within the first 3 months of diagnosis were included in this study; 93.2% of these patients experienced skin toxicities. Approximately 70% of the patients developed xerosis and pruritus, while 50% had papulopustular eruptions and paronychia. The mean skin symptom impact score was 5.38 (standard deviation = 2.65). The skin-related quality of life varied widely among the participants but remained acceptable (mean score = 13.96, standard deviation = 16.55). Skin symptoms correlated significantly with poor quality of life (r = 0.50, P  < .001). Younger patients and those treated with afatinib were the most affected, reporting the poorest quality of life. Patients who required EGFR-TKI dose reduction had experienced more severe skin symptoms than had patients who did not require it (7.35 vs 5.01, P  < .001). Skin toxicity related to EGFR-TKI treatment impacts the quality of life in patients with NSCLC. During the treatment period, skin assessment and tailored management should be incorporated into the daily care plan.